International practices in health technology assessment and public financing of digital health technologies: recommendations for Hungary - Mezei, Fruzsina; Horváth, Krisztián; Pálfi, Máté; Lovas, Kornélia; Ádám, Ildikó; Túri, Gergő (Frontiers in Public Health, 2023)
Background: Evaluating and iIntegratingmplementing appropriate ddigital health technologies is a critical component of a national healthcare ecosystem in the 2020s2020s and is expected to even increase in significance. . Design: The paper gives an overview of international practices on public financing and health technology assessment of digital health technologies (DHTs) in five European Union (EU) countries and outlines recommendations for country-level action that relevant stakeholders can consider in order to support uptake of digital health solutions in Hungary. A scoping review was carried out to overview identify and gather country-specific classifications and international practices on the financing DHTs in five pioneering EU countries: Germany, France, Belgium, the United Kingdom and , Finland.Results: Several While several evaluation frameworks have been developed for DHTs exist already, however there is no single, unified framework or method for classification, evaluation, and financing of digital health technologies in the in European contextEuropean Union. European countries apply different taxonomy, use different assessment domains and regulations for the reimbursement the This is a provisional file, not the final typeset article payment of DHTs. The Working Group of the Hungarian Health Economic Society recommends on eight specific action points for stakeholders, including importantly taking part active role in shaping common clinical evidence standards and technical quality criteria across Europe in order for common standards to be developed in the European Union single market.s to be implemented. Conclusion: Specificities of national healthcare contexts must be taken into account in decisions to allocate public funds to certain therapies rather than others.